Intravenous Penicillin for Antenatal Syphilotherapy - Henry L. Galan; Paul M. Yandell; Alfred B. Knight (Hindawi Limited, 1993)
A 21 year old woman (G2 P0101) of 24 weeks gestation presented with syphilis of unknown duration. Sonography revealed fetal hydrops and placental thickening. Weekly intramuscular injections of 2.4 million U Bicillin for 3 weeks was initiated as recommended by the Centers for Disease Control. Repeat sonogram 1 week after starting treatment revealed increased ascites and a new pericardial effusion. Due to the worsening fetal condition, therapy was altered and the patient was admitted for IV penicillin. She received a continuous infusion of 18 million U penicillin G daily for 10 days. Serial sonograms showed improvement offetal ascites and pericardial effusion with 10 days of IV therapy, and complete resolution of hydrops was noted within 3 weeks. The fetus was born at term with no stigmata of congenital syphilis on newborn exam, and laboratory tests suggested adequate treatment in utero.